Using conformational sampling to model spectral and structural changes of molecules at elevated pressures - Zeller, Felix; Pracht, Philipp; Neudecker, Tim (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2025)
Conformational sampling is nowadays a standard routine in computational chemistry. Within this work, we present a method to perform conformational sampling for systems exposed to elevated pressures within the CREST program, allowing us to model pressure-induced changes of molecular ensembles and structural parameters. For this purpose, we extend the molecular Hamiltonian with the PV (pressure times volume) term, using the solvent-accessible volume. The volume computation is performed within the new standalone library libpvol. A first application shows good agreement with experimental data and provides a reasonable explanation for severe pressure-induced structural and spectroscopic changes of the molecules dichloroethane and tetra(4-methoxyphenyl)ethylene.
Online veröffentlicht: 12. Februar 2025
Gesehen am 24.07.2025